Hirschsprung disease as a yet undescribed phenotype in a patient with ARID1B mutation. Issue 12 (11th August 2016) - Takenouchi, Toshiki; Yoshihashi, Hiroshi; Sakaguchi, Yuri; Uehara, Tomoko; Honda, Masataka; Takahashi, Takao; Kosaki, Kenjiro; Miyama, Sahoko
Abstract : Mutations in the BAF complex (mammalian SWI/SNF complex) are responsible for Coffin‐Siris syndrome, which is characterized by developmental delay, distinctive facial features, hirsutism, and hypoplasia/aplasia of the fifth finger/fingernails. Hirschsprung disease is characterized by defective stem cells in the enteric neural system, and the involvement of multiple signaling cascades has been implicated. So far, the roles of the BAF complex in the genesis of Hirschsprung disease have remained unknown. Here, we document a patient with coarse facial features, postnatal growth failure, developmental delay, epilepsy, and hypoplasia of the corpus callosum and cerebellum but without a hypoplastic fifth finger/fingernail. In addition, he had Hirschsprung disease. Exome sequencing with a gene set representing a total of 4, 813 genes with known relationships to human diseases revealed a heterozygous frameshift mutation in ARID1B (c.5789delC p.Pro1930Leufs*44). The presence of a congenital cataract and Hirschsprung disease in the presently reported patient further expands the phenotypic spectrum of patients with ARID1B mutations and may suggest the potential role of the BAF complex in the pathogenesis of the enteric neural system. The present observation is in agreement with a recent study of Drosophila neuroblasts showing that the dysregulated BAF complex leads to an abnormal lineage progression of neural stem cell lineages and that Hirschsprung disease is caused by abnormal stem cell lineages in the peripheral neural tissues. © 2016 Wiley Periodicals, Inc.